STRENGTHENING SANITATION REGULATIONS: MEASURING THE EFFECTIVENESS OF ENVIRONMENTAL SANCTIONS FOR DOMESTIC WASTEWATER MANAGEMENT IN DENSELY POPULATED AREAS - Gautama, Elly Christanty; Tuhuteru, Justian Stanley; Issalillah, Fayola; Mardikaningsih, Rahayu; Hardyansah, Rommy (Gapenas Publisher, 2025)
The management of domestic wastewater in densely populated areas is a critical issue situated at the intersection of public health policy and environmental law in Indonesia. This normative juridical research aims to analyze the legal construction of obligations for domestic wastewater management and the effectiveness of the environmental sanction system in fostering compliance within densely populated zones. The findings indicate that a comprehensive legal framework has been established through a regulatory hierarchy, beginning with the 1945 Constitution, Law No. 32 of 2009 concerning Environmental Protection and Management, Law No. 36 of 2009 concerning Health, and extending to various technical regulations such as Minister of Environment and Forestry Regulation No. P.68/2016 on Domestic Wastewater Quality Standards. Legal obligations are imposed reciprocally upon the state to provide systems and upon the community to comply. Regarding enforcement, a sanction system encompassing administrative, civil, and criminal penalties has been established under the Environmental Protection and Management Law. However, the effectiveness of this sanction system within the context of densely populated areas remains limited. This limitation is attributed to factors such as limited monitoring and evidentiary capacity, the absence of adequate alternative infrastructure, and prevailing socio-economic constraints within the community. This study concludes that successful sanitation law enforcement requires an integrative approach, combining sanction instruments with infrastructure provision, institutional strengthening of oversight, and sustained public education.